2007
DOI: 10.1148/radiol.2431051825
|View full text |Cite
|
Sign up to set email alerts
|

Extramural Depth of Tumor Invasion at Thin-Section MR in Patients with Rectal Cancer: Results of the MERCURY Study

Abstract: Demonstration of accurate measurement of the depth of extramural tumor spread in the MERCURY Study enabled accurate preoperative prognostication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
1
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(78 citation statements)
references
References 32 publications
2
71
1
4
Order By: Relevance
“…In this study, we lack confirmation of radiological result with pathologic reference standard for the actual depth of extension (T3 sub-staging), but in our defense, a study revealed high agreement (92%) up to 0.5 mm for extramural tumor extension between radiologic and histopathologic diagnosis (11), and this is a reproducibility study rather than accuracy study. Therefore, it should not be criticized from that point of view.…”
Section: Limitations Of Our Studycontrasting
confidence: 54%
See 1 more Smart Citation
“…In this study, we lack confirmation of radiological result with pathologic reference standard for the actual depth of extension (T3 sub-staging), but in our defense, a study revealed high agreement (92%) up to 0.5 mm for extramural tumor extension between radiologic and histopathologic diagnosis (11), and this is a reproducibility study rather than accuracy study. Therefore, it should not be criticized from that point of view.…”
Section: Limitations Of Our Studycontrasting
confidence: 54%
“…Recently, using 5 mm as a cutoff point to differentiate early and advanced T3 rectal cancer is highly acceptable. According to recent studies, patients with a DME more than 5 mm should be identified properly because they have a worse prognosis compared to patients with DME less than 5 mm (11).…”
Section: Introductionmentioning
confidence: 99%
“…Axial images are also obtained before gadolinium administration. study, extramural depth of spread was predicted accurately with thin-section MRI (within 0.5 mm error compared to histopathologic extramural depth of spread) (31). Extramural vascular invasion (EMVI) is another prognostic factor in rectal cancer, which is associated with high risk of local and distant recurrence (32) and poor overall survival (33).…”
Section: Accuracy Of Mrimentioning
confidence: 99%
“…The extent of tumour spread from the muscularis propria is easily measured and has been underestimated for its value as a predictor of high-risk disease. It is quantifiable and readily reproducible on MRI [35], just as mesorectal fascial involvement is [36]. In addition to adverse prognostic factors, there are good prognostic markers such as a pushing border to the invasive front, a high normal lymph node yield, a dense lymphocytic infiltrate surrounding the tumour and a high tumour cell density accompanied by a low stroma content.…”
Section: Microscopic Featuresmentioning
confidence: 99%